Provision of renal care for patients with end stage kidney disease in persistent vegetative state, in United Arab Emirates: a national survey of renal physicians. Issue 1 (1st January 2018) - Alshamsi, Fayez Ebrahim; Chaaban, Ahmed; Alrukhaimi, Mona; Bernieh, Bassam; Bakoush, Omran
ABSTRACT: Patients with end stage kidney disease (ESKD) with severely impaired cognitive function have no survival benefit from dialysis. We therefore undertook a survey to explore the renal physicians' practices of withholding and withdrawal of dialysis treatment in vegetative state patients in the United Arab Emirates (UAE). A cross sectional survey of 29 nephrology practices in UAE exploring physicians' practices in making decisions of withholding and withdrawal of dialysis treatment during provision end-of-life care for patients in persistent vegetative state (PVS).The majority of participants practice in governmental non-for-profit dialysis units (79%), and think they are well prepared to make decision with patients and family on issues of dialysis withdrawal and withholding (69%). If a chronic dialysis patient became permanently unconscious only few respondents (17%) indicated probability of stopping dialysis. On the other hand, more respondents (48%) reported that dialysis is likely to be withheld in PVS patients who develop kidney failure. In high risk or poor prognosis ESKD patients and given how likely they would consider each option independently, respondents reported they are likely to consider time-limited dialysis in 78% of the time followed by stopping (46%) or forgoing (27%) dialysis. Majority of the participants perceived that their decisions in providing renal care for PVS patients in UAE were influenced by the family sociocultural beliefs (76% of participants), the current hospital policies (72% of participants), and by Islamic beliefs (66% of participants). Only few perceived access to palliative care (30%) and treatment cost (17%) to have an impact on their decision making.Decisions of initiation and continuation of dialysis treatment to ESKD patients in PVS are prevalent among nephrology practices in UAE. Development of local guidelines based on the societal values along with early integration of palliative kidney failure management care would be required to improve the quality of provision of end-of-life renal care in UAE. Abbreviations : ESKD: stage kidney disease; UAE: United Arab Emirates; PVS: persistent vegetative state; RPA: Renal Physicians Association; ASN: American Society of Nephrology; EMAN: Emirates Medical Association Nephrology Society; CPR: cardiopulmonary resuscitation.